Evaluasi Penerapan Good Governance pada Laporan Pertanggungjawaban Alokasi Dana Anggaran - Janardana Ramendra; Putu Sukma Kurniawan (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
Good governance is a target that every village wants to achieve. Transparency, accountability, efficiency, effectiveness, and participation will foster good governance. The objective of this research is to describe the application of Good Governance in the accountability report for managing village funds, to describe the constraints in implementing Good Governance, and to describe solutions in implementing Good Governance in the accountability report for managing village funds in the area of Padangbulia Village. This research is a descriptive research design. The data that used in this research are primary data. Data collection techniques in this research were interviews and documentation. This research uses triangulation techniques to check the validity of the data. Theoretically, Padangbulia Village has applied the concepts of Good Governance to the management of village fund allocations even the financial statement are still not accordance with Pemendagri No. 37 of 2007.